Fish Stock Condition in Southern Coastal Water of West Java - Setyo Budi Susilo (Jurnal Ilmu-Ilmu Perairan dan Perikanan Indonesia, 2009)
Fish stock in marine waters is always dynamic due to fluctuation in the annual total catch. Consequently, the estimate number of fish stock changes yearly, without exception in the southern coastal water of West Java. Fish stock condition in this region has not been reevaluated since 1999, the time before the separation of the province into West Java and Banten. This current study was intended to reassess the condition of fish stock utilization and estimate fish stock growth parameters in the southern coastal water of West Java in 2006. Data of fish production, effort, fish price, and effort cost for 14 years (1993-2006) are taken from the Office of Fisheries Agency of West Java Province. Effort data are standardized using relative fishing power method. Analysis of fish stock condition is carried out using Gordon-Schaefer bioeconomic model. Fish stock growth parameters are estimated using CYP, Uhler, and Hilborn and Walters methods. The results showed that utilization of marine fish resource in the southern coastal water of West Java is still in the condition of underfished and under effort. Estimates of fish stock growth parameters in this area are r = 3.8882, K = 22 080.355 ton, and q = 14.1775 × 10-7.Key Words: Fish stock assessment, southern coastal water, West Java, Gordon-Schaefer model.